2020
DOI: 10.1002/er.5707
|View full text |Cite
|
Sign up to set email alerts
|

Ultrahigh voltage and energy density aluminum‐air battery based on aqueous alkaline‐acid hybrid electrolyte

Abstract: Thanks to the high theoretical capacity and energy density, abundant resource, low-cost, and environmental friendliness, aluminum-air battery (AAB) has attracted research interests driven by the promise for electricity generator. However, low operating voltage leads to low practical energy density, and restricting the applications of AAB. In this study, the concept of an ultrahigh voltage AAB based on aqueous alkaline-acid hybrid electrolyte is introduced and demonstrated. Meanwhile, the working mechanism is i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 57 publications
0
13
0
Order By: Relevance
“…Figure f shows the polarization curve of the batteries with different inhibitors. It could be observed that the batteries show a similar activation process at the low-current-density region . The peak power densities of the batteries without and with ZnO and hybrid inhibitors are 49.6, 51.3, and 63.7 mW cm –2 , respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure f shows the polarization curve of the batteries with different inhibitors. It could be observed that the batteries show a similar activation process at the low-current-density region . The peak power densities of the batteries without and with ZnO and hybrid inhibitors are 49.6, 51.3, and 63.7 mW cm –2 , respectively.…”
Section: Results and Discussionmentioning
confidence: 99%
“…It could be observed that the batteries show a similar activation process at the low-currentdensity region. 36 The peak power densities of the batteries without and with ZnO and hybrid inhibitors are 49.6, 51.3, and 63.7 mW cm −2 , respectively. However, the peak power density of the batteries with 18 g L −1 AM is 46.3 mW cm −2 (Figure S5d).…”
Section: Dischargementioning
confidence: 98%
“…Metal-air batteries (MABs), with the advantages of low cost, high energy density, large capacity, and less dependence of capacity on workload and temperature, have attracted much attention. [1][2][3][4][5] MABs convert chemical energy into electricity by consuming metals and oxygen in the air, making them an ideal clean energy source. [6][7][8] Thereinto, on account of the high electrochemical equivalent (2.98 Ah/g) and volume-specific energy (8.04 Ah cm À3 ) of aluminum, the aluminum-air battery (AAB) has the actual specific energy of 900 Wh/kg, 9 and the theoretical specific energy of AAB can reach 8100 Wh/kg, 10 which is second only to lithium-air batteries in all MABs.…”
Section: Introductionmentioning
confidence: 99%
“…Metal‐air batteries (MABs), with the advantages of low cost, high energy density, large capacity, and less dependence of capacity on workload and temperature, have attracted much attention 1‐5 . MABs convert chemical energy into electricity by consuming metals and oxygen in the air, making them an ideal clean energy source 6‐8 .…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23][24][25][26][27][28][29] The photo-battery is a typical example of an integrated solar energy conversion and storage device that utilizes solar energy to power electric vehicles and smart phones. [30][31][32][33][34][35][36][37][38][39] The electric vehicles require fixed charging point to charge the lithium-ion battery, which is detrimental to the portability and endurance of the device; such issues can be solved by the development of the photo-battery materials that help charge the batteries in the electric vehicles remotely via the solar energy. The development of the photo-batteries is beneficial for the Internet-of-Things (IoT) that require individual devices to be powered remotely.…”
Section: Introductionmentioning
confidence: 99%